1946
DOI: 10.5254/1.3543264
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nature of the Rubber-To-Brass Bond

Abstract: In the initial stages of the reaction at the rubber-brass interface, formation of cuprous sulfide takes place. After this compound is formed, three possible reactions can occur. (1) The cuprous sulfide can unite with a “free” sulfur atom to form cupric sulfide. (2) The cuprous sulfide can attach itself to a sulfur atom already combined with the rubber. (3) The cuprous sulfide can attach itself directly to the rubber at points of unsaturation. In all cases of bad bonding brass examined by physical means, failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1963
1963
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Adhesion can be described as the interatomic and intermolecular forces at the interface of two surfaces but in reality, it is very complex phenomenon implicating a multidisciplinary knowledge. Numerous studies have been performed on adhesion to describe it, to explain how it works and how it can be predicted as it is a key aspect in the protection offered by coating [38][39][40][41][42][43][44]. Several theories exist to explain adhesion but the aim of this paragraph is not to review them and detailed information can be found elsewhere [38][39][40][41][42][43][44].…”
Section: Adhesion: a Protective Mechanism Or A Pre-requisite For Corrmentioning
confidence: 99%
“…Adhesion can be described as the interatomic and intermolecular forces at the interface of two surfaces but in reality, it is very complex phenomenon implicating a multidisciplinary knowledge. Numerous studies have been performed on adhesion to describe it, to explain how it works and how it can be predicted as it is a key aspect in the protection offered by coating [38][39][40][41][42][43][44]. Several theories exist to explain adhesion but the aim of this paragraph is not to review them and detailed information can be found elsewhere [38][39][40][41][42][43][44].…”
Section: Adhesion: a Protective Mechanism Or A Pre-requisite For Corrmentioning
confidence: 99%
“…The electronic theory suggested by Deryaguin (1948) and Deryaguin (1957) and known as electrical double layer, electrostatic or parallel plate capacitor theory attributes adhesion to electrostatic phenomenon. Buchan (1946) suggested a theory based on chemical bonding. They assessed that adhesion is based on covalent chemical bonding appearing at the interface between two materials.…”
Section: Theory Of Adhesionmentioning
confidence: 99%
“…Firstly, the electrostatic attraction model proposed by Derjaguin and Smilga in 1967 [11] , this model considers a charge transfer when two materials of different natures are brought into contact. Secondly, the adhesion by chemical bonds proposed by Buchan in 1946 [12] . Sometimes it is possible to create covalent or ionic bonds at the interface between the adhesive and the substrate through chemical reactions.…”
Section: Introductionmentioning
confidence: 99%